Can growth be optimized in enterally fed very low birth weight infants who receive dexamethasone as compared to untreated peers: a retrospective study - Melissa Thoene; Stacy Souerdyke; Elizabeth Lyden; Ruomei Wu; Kara Weishaar; Elizabeth Elliott; Katelyn White; Ann Anderson-Berry (Hygeia Press di Corridori Marinella, 2018)
Background: Growth is essential for very low birth weight infants, but is compromised in those receiving dexamethasone, especially when given as a consecutive 10-day treatment course to wean ventilatory support. The purpose of this review is to analyze growth outcomes of enteral nutrition practices for infants born < 1,500 grams who received at least one consecutive 10-day treatment course during hospitalization compared to untreated peers. Methods: An IRB-approved retrospective chart review compared 17 dexamethasone-treated study infants vs. 34 untreated controls born < 1,500 grams. Wilcoxon rank sum test and Fisher's exact test compared continuous data and associations of categorical variables. Multiple regression analyzed predictors for growth outcomes when adjusting for birth gestational age. P-value < 0.05 was considered statistically significant. Results: Treated infants were born younger (25+4 vs. 27+6 weeks gestational age [GA]) with smaller anthropometric measurements (p < 0.05). Growth from birth to 36 weeks GA approached significance (15.1 grams/kg/day study vs. 16.65 grams/kg/day control [p = 0.07]). Treated infants were discharged at similar weight percentiles as untreated infants (p = 0.7). Head growth percentiles were well-maintained for all infants (treated: median 12th% birth, 21st% discharge; untreated: 29th% birth, 43rd% discharge). Treated infants had lower length measurements at 36 weeks GA (p = 0.011) and discharge (p = 0.095). Treated infants received more nutrition, median 131 vs. 119 calories/kg/day (p = 0.0005), 4.4 vs. 4.1 grams protein/kg/day (p = 0.0004). Average nutrition delivery during dexamethasone treatment was 138 calories/kg/day, 4.5 grams protein/kg/day. There were no differences in highest blood glucose (p = 0.071), BUN (p = 0.053), or alkaline phosphatase (p = 0.17) between groups. Conclusions: Infants receiving at least one consecutive 10-day treatment course with dexamethasone during hospitalization experienced altered growth by 36 weeks GA, but comparable growth to non-treated infants for weight and head circumference can be achieved by discharge by optimizing enteral nutrition before, during, and after dexamethasone treatment. Future studies are needed to assess if this leads to improved developmental outcomes.